TASHQI SAVDONI BOJXONA TOMONIDAN TARTIBGA SOLISHDA NOTARIF CHORALARNI QOʻLLASHNING DOLZARB MASALALARI (Marketing Journal, 2026)
AbstractThe article examines the importance of non-tariff regulation of foreign trade as aneffective tool for managing trade and political relations. It analyzes the need to considerthe potential for imbalances in supply and demand within the country whenestablishing quantitative restrictions on export and import quotas, provided theeconomic conditions for their application exist. Recommendations for improving theuse of quotas in customs regulation of foreign trade in our country are developed.Keywords: non-tariff measures, quota, export quotas, import quotas, quotavolume, foreign trade.